A meta-analysis of the relationship between bullying and non-suicidal self-injury among children and adolescents - Huang, Haitao; Ding, Yueming; Wan, Xiao; Liang, Yipei; Zhang, Yiming; Lu, Guangli; Chen, Chaoran (Scientific reports, 2022)
Non-suicidal self-injury (NSSI) has attracted increasing attention due to its high detection rate, high risk and high repeatability. There is a need for the early identification of preventable occurrence factors, which is necessary to facilitate screening and intervention, especially to facilitate the early detection of high-risk individuals. This research aims to investigate the relationship between bullying behaviour and non-suicidal self-injury among children and adolescents by means of meta-analysis. The PubMed, Embase, Web of Science, SCOPUS, PsycINFO, CKNI and WAN FANG databases were searched from inception to 14 December 2021 for studies that explored the relationship between bullying behaviour and NSSI among children and adolescents. A total of 29 articles met the inclusion criteria of the meta-analysis, and 54 independent effect sizes were obtained, including 53,501 subjects. Victims [OR 2.46 (95% CI 2.14–2.83); p < 0.001], bullies [OR 2.12 (95% CI 1.37–3.27); p < 0.001], and bully-victims [OR: 2.98 (95% CI 1.85–4.82); p < 0.001] were more likely to have NSSI than uninvolved children or adolescents. In addition, analyses showed the absence of publication bias. In the victim group, the older the age was, the lower the risk of NSSI (z = − 3.74, p = 0.00). Gender does not play a moderating effect on the association between bullying behaviour and non-suicidal self-injury. The relationship between involvement in bullying and NSSI was demonstrated. By taking measures to prevent bullying, the incidence of NSSI in children and adolescents can be potentially reduced.